Assessing instrument reliability and research feasibility for EFL learner autonomy: evidence from a pilot study in Xi’an, China - Cao, Xiaojun; Wan Mohamed, Wan Nazihah; Yusoff, Muhammad Saiful Anuar (Universiti Teknologi Mara Cawangan Pulau Pinang, 2026)
It is important that the instruction of English as a Foreign Language (EFL) requires an understanding of how learning styles, learning engagement, and learner autonomy interact. Valid instruments are prerequisites for the research, especially in Chinese cultural contexts. The purpose of this pilot study is to evaluate the feasibility of research methods and validate the psychometric qualities of three modified scales that measure learning styles, learning engagement, and learner autonomy among non-English major undergraduates in Xi’an, China. The current study used a quantitative cross-sectional design and convenience sampling. One hundred undergraduates completed the online survey via the WJX platform. Recruitment rates, completion times, and data quality evaluated the study feasibility. The instrument reliability was evaluated by Cronbach’s alpha. Bilingual professionals examined the translated instruments’ cultural appropriateness. With a 71.4% response rate, a mean completion time of 12.4 minutes, and no missing data, the recruitment and response procedures were practical. All the Cronbach’s alpha values for learner autonomy, learning styles, and learning engagement exceeded 0.90, showing the instruments have outstanding internal consistency. The results validate the high reliability and cultural appropriateness of the instruments for the target population, as well as the suggested research methods. This pilot study offers a strong methodological basis for a more thorough examination of the connections between these constructs in the context of Chinese EFL.